DAKWAH DAN DIMENSI SOSIAL - Kusnadi, Kusnadi; Mujdalifa; Abbas, Nurhafifah (LP2M IAIM Sinjai, 2025)
Dawah is a vital activity in Islam that is not limited to religious aspects, but also has a broad social dimension. Dawah aims to build a just, prosperous, and harmonious society. This study aims to understand the concept of dawah and social dimension, as well as the role of dawah in building social awareness and addressing social problems. This study uses a qualitative approach with a literature review method. The primary data sources are journal articles that discuss dawah and social dimension. The results show that dawah has an important role in building social awareness, addressing social problems, and building a more prosperous society. Dawah must be carried out by considering the social conditions of the community and interacting with various aspects of social life. Dawah and social dimension are two interrelated concepts that cannot be separated. Dawah can be an effective means of building a harmonious, just, and prosperous society if carried out in a wise and gentle manner